Characterization of the surface macrophages of the avian lung with observations on a phagocytic respiratory epithelium. - Liliane Nganso, Nganpiep (My University, 2001)
Due to paucity of free respiratory macrophages (FRMs), compared with mammals, birds have been alleged to be more susceptible to pulmonary infections and affliction. The goal of this study was to question or validate this speculation. Twenty-two mature healthy chickens, 24 domestic ducks and 20 rats were used in various experiments. After pulmonary lavage, FRMs were stained with trypan blue for cell count and with neutral red and trypan blue to assess cell longevity. The cell dynamics was determined by counts made on serial lavages. The morphological attributes of the FRMs and that of the respiratory “phagocytic epithelium” were quantified stereo logically. The rat had a significantly greater number of macrophages and the surface density of the filopodia of the FRMs was higher than that of the birds. The volume density of the vesicular bodies of the macrophages in the three groups of animals was not significantly different. Putative cell flux onto the respiratory surface was observed in the birds and not in the mammal. The surface area of the “phagocytic epithelium” of the birds was very extensive. Compared with mammals, in general, FRMs are fewer in birds. Despite this, the pulmonary defensive status in birds may not necessarily be compromised: functionally, avian FRMs appear to be more efficient. Moreover, their defense function is complimented particularly by the phagocytic activity of the epithelium immediate to the blood-gas barrier, the most vulnerable site of the lung-air sac system.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Anatomical Sciences.
Keywords: Macrophages; Alveolar/physiology; Alveolar/cytology